Relationship between Sleep Quality and Heart Attacks Incidents among Infarct Myocard Acute Patients at Ulin Banjarmasin Hospital - Zainab; Ningsih, Endang Sri P; Yuspitasari, Dyah (School of Nursing, Faculty of Medicine and Health Science, Universitas Lambung Mangkurat, 2018)
The various clinical symptoms among IMA patients (Infarct Myocard Acute) are chestpain during activity, dyspnea, lethargy and disruption of rest and sleep. These symptompshave impact on rest and sleep disturbance. Sleep disturbances increases adrenaline thatstimulate of heart work, constrict blood vessels, and also heart attacks.The aim of this study was to determine the relationship between sleep quality andincidence of heart attacks among patients with infarct myocard acute at Ulin HospitalBanjarmasin. This study used correlative study with accidental sampling technique. Totalsample was 35 patients in RSUD Ulin Banjarmasin. The instrument was used to measurethe quality of sleep were adopted from The Pittsburgh Sleep Quality Index (PSQI), andincidents of a heart attack was measured by record observations on the medical record.The results of this study showed that good sleep quality was 22.9%, poor sleep qualitywas 77.1%. Respondent with re-attack was 57.1% and initial attack was 42.9%.Statistical analysis with fisher exact test showed p-value was 0.000, hence there wascorrelation between sleep quality and incidence of heart attack among IMA patients atUlin Hospital Banjarmasin. It is important for nurses to facilitate and conductintervention in term of patients’ rest needs in order to improve sleep quality.